2021
DOI: 10.1097/ajp.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain-derived Neurotrophic Factor From Active and Sham Transcranial Direct Current Stimulation in Older Adults With Knee Osteoarthritis

Abstract: Objectives: Previous work has shown effects of transcranial direct current stimulation (tDCS) on clinical pain measures, qualitative sensory testing measures, and peripheral inflammation. The present report extends this research to investigate the effect of tDCS on brain-derived neurotrophic factor (BDNF) levels.Materials and Methods: This secondary analysis examined a sample of 40 older adults (50 to 70 y old) with symptomatic knee osteoarthritis randomly assigned in a 1:1 fashion to active (n = 20) or sham (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Recently, Dimmek et al detected that in OA-related chronic widespread pain patients, reduced serum BDNF levels may induce the anxiety and depression via affecting the function of immune cells ( 27 ), which supported the present findings on relationships of BDNF with depression and pain. Additionally, previous studies showed serum/plasma BDNF levels can elevated in OA patients after the continuous non-surgical treatment, with improving the pain symptom ( 28 , 29 ), which suggested that BDNF levels can be affected by the severity of OA. Similarly, the present study observed that in the development of OA, lower serum BDNF levels reflected the more serious of pain and predicted the high risk of MDD.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Dimmek et al detected that in OA-related chronic widespread pain patients, reduced serum BDNF levels may induce the anxiety and depression via affecting the function of immune cells ( 27 ), which supported the present findings on relationships of BDNF with depression and pain. Additionally, previous studies showed serum/plasma BDNF levels can elevated in OA patients after the continuous non-surgical treatment, with improving the pain symptom ( 28 , 29 ), which suggested that BDNF levels can be affected by the severity of OA. Similarly, the present study observed that in the development of OA, lower serum BDNF levels reflected the more serious of pain and predicted the high risk of MDD.…”
Section: Discussionmentioning
confidence: 92%
“…Full texts of 33 records were evaluated, and finally, 13 RCTs met the inclusion criteria (Figure 1). [19][20][21][22][27][28][29][30][31][32][33][34][35] The reasons for excluded trials appear in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 13 RCTs were included, with sample sizes ranging from 15 to 60, but that does not mean that there is quantitive evidence from 13 trials for every outcome measure (pain, physical function, stiffness, mobility performance, quality of life, pressure pain tolerance, and plasma levels of BDNF). The individuals included within studies by Ahn et al, 19,27 Suchting et al, 17,32 Geraldine (1) et al, 34 and Geraldine (2) et al 35 were repeated. However, different outcomes and measuring method of outcomes were reported in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While still embryonic, research suggests that BDNF levels, for instance, could highlight pain inhibition and neuroplastic changes, thus illustrating treatment response [ 33 ]. Of note, we previously found a relationship between BDNF, heat pain threshold, and clinical pain (numeric rating scale) in individuals with knee OA [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%